Capacity utilisation average cost and profitability: A sector-wise analysis of block rubber processing industry in India - George K T; Kumaran M G (Indian Journal of Natural Rubber Research, 1990)
Relationships among capacity utilisation, average cost and profitability in the block rubber processing factories in the estate and non-estate sectors have been examined based on a cross-sectional analysis of 12 units producing block rubber in 1987-88. In terms of capacity utilisation and average cost of processing, factories in the non-estate sector were performing better than their counterparts in the estate sector. However, the non-estate sector had a higher average unit over-head and admininstrative cost and a relatively lower profitability in spite of its higher average unit over-head and administrative cost and a relatively lower profitability in spite of its higher capacity utilisation and average unit cost in the industry was found to be insignificant. Results of the study showed the influence of various extraneous factors contributing to the divergence in the behaviour of selected parameters. Policy imperatives emerging from the study call for re-organisation in the existing combinations of machinery, mode of raw material procurement and nature of raw material processed.
Keywords: Block rubber; Block rubber; Capacity utilisation; Capacity utilisation; Cost analysis; Cost analysis; Estate sector; Estate sector; Installed capacity; Installed capacity; Non-estate sector; Non-estate sector; Profit analysis; Profit analysis; Rubber processing industry; Rubber processing industry